Origem e evolução do sistema de fluidos relacionados à deposição dos veios Rato, Tatá e Otta do Depósito de Ouro de Santa Cecília, porção centro-sul da Província Aurífera de Alta Floresta (PAAF) no sudoeste do Cráton Amazônico - Felber, Antonio Gabriel Fornarolli (2017)
The Santa Cecilia gold deposit is located in the south-central portion of the Alta Floresta Gold Province, southwest portion of Amazon Craton in the north of Mato Grosso. The deposit is formed by three gold mineralized quartz veins known as Otta, Tatá and Rato. The first two are hosted in an isotropic granodiorite while the latter in a locally foliated metadacite. Hydrothermal alteration is similar for the veins and developed in six stages respectively: sericitic, potassic, muscovite+pyrite, calcic, silicification 1 and silicification 2, with gold deposited in the last silicification stage. The quartz veins occur slightly to intensely recrystallized. Sulfides occur within the quartz veins and consists of pyrite, pyrrhotite, arsenopyrite, chalcopyrite and sphalerite. Fluid inclusion petrography in the veins revealed the presence of five Fluid Inclusion Assemblage (FIA). FIA 1 and 2 in the Rato vein, FIA 3 e 4 in the Tatá vein, and FIA 5 in Otta vein. FIA 1 is primary, aqueous-carbonic, two-phase and present chlatrate melting temperature ranging from -5,1 to +1,1 °C, with the calculated salinity ranging from 12 to 20 wt% NaCl, total homogenization temperature – Th (total) – from 220 to 450°C with a mode at 360°C. FIA 2 is secondary, aqueous, two-phase, with Te in the range of -42° to -25,1°C, suggesting a H2O-NaCl system with variations to KCl, MgCl2 and FeCl2. The ice melting temperature – Tm (ice) – range from -2,6 to -20,8°C reflecting salinities between 4,34 to 22,91 wt% NaCl equiv. and Th (total) from 155 to 300°C with a mode around 240°C. FIA 3 and 4 are aqueous, two-phase, and respectively of primary and pseudo-secundary origin. FIA 3 shows Te ranging from - 21,2 to -39 °C suggesting a H2O-NaCl system with variations to KCl, MgCl2 and FeCl2. Tm (ice) ranges from -6,5 to -20,7 °C, calculated salinity between 9,86 to 22,85 wt% NaCl equiv. and Th (total) from 166 to 252°C, with a mode around 200°C. FIA 4 shows Te between -24,6 to -44,4°C, suggesting a H2O-NaCl-KCl system with variation to MgCl2 and FeCl2, Tm (ice) ranges from -6,3 to -20,9°C, calculated salinity between 9,6 and 22,98 wt% NaCl equiv. and Th (total) from 198 to 267°C. FIA 5 is represented by primary, two-phase aqueous inclusions with Te ranging from -22 to -24,7°C and Tm (ice) ranging from -0,8 to -7°C. The Te suggests a H2O-NaCl system with variation to KCl. Th (total) range from 185 to 290°C, with a mode around 200°C and the calculated salinity ranges from 1,4 to 10,49 wt% NaCl equiv. Oxygen isotopic analyzes in quartz returned values of δ 18O of 13,27‰, 12,46‰, e 13,70‰ respectively for Rato, Tatá and Otta veins. The isotopic compositions of the quartz equilibrium fluids were calculated based on the end-member’s values of Th (total) variation for each vein and respectively returned values of δ 18O between +3,07‰ e +10,07‰, -1,64‰ e +3,56‰ e +1‰ e 7,8‰; the obtained variation suggests the existence of magmatic and meteoric sources. Fluid inclusion data suggests a sequential evolution/release of a CO2-rich saline fluid possibly magmatic to a CO2-poor/free aqueous saline fluid, which during evolution mixed with a low-salinity aqueous fluid, likely meteoric in origin, and underwent a boiling process; this set of processes possibly led to the gold deposition. The depth boiling depth calculated at 300 meters for FIA 2, 150 meters for FIA 5 and 100 meters for FIA 3 and boiling pressure at 30, 14 and 13 bars, respectively. Characteristics such as hydrothermal alteration zones forming narrow halos around the veins, the small volume of the reduced sulfide assembly, inclusions of moderate to high salinity likely of magmatic origin, as shown by the oxygen isotope data, suggest that the Santa Cecília deposit resembles mainly the intrusion-related gold systems (IRGS) model. LA-ICP-MS zircon U-Pb ages of 1816 Ma for hosting granodiorite suggests a correlation with the gold-bearing Paranaíta Suite while the age 1895 Ma for the metadacite suggests a southwest extension of the Tapajós-Parima province into the northern Mato Grosso state.